Integrating the TGT Model and Wordwall: An Innovative Approach to Biology Instruction on the Endocrine System Topic : Mengintegrasikan Model TGT dan Wordwall: Pendekatan Inovatif untuk Instruksi Biologi pada Topik Sistem Endokrin - Anisa, Anisa; Aziz, Andi Gunawan; Magfirah, Nurul (BIO-EDU: Jurnal Pendidikan Biologi, 2025)
This research aims to examine the effect of using the Team Games Tournament learning model combined with Wordwall media on student motivation and learning outcomes. This research is a quantitative type of quasi-experimental research. This research design uses a Control Group Pretest-Posttest Design. The population in this study were all students in class XI MIPA at SMAN 10 Makassar, consisting of 8 classes with 254 students. The sampling technique is random sampling, namely random sampling where all classes have the same possibility of being sampled. Class XI MIPA II as an experimental class had 22 students and class XI MIPA VI as a control class had 22 students. The data analysis techniques used in this research are descriptive analysis and inferential statistical analysis in the form of normality, homogeneity and independent hypothesis testing t - tests. The results of this study show that there is a difference in the questionnaire scores in the experimental class, which is in the high category with an average of 91 and in the control class, it is in the sufficient category with an average of 58 and the learning outcomes scores of experimental class students are with an average of 85.55 and The average in the control class is 77.55, where the learning outcomes of experimental class students are higher than those in the control class. It can be seen by looking at the results of the hypothesis test which shows a sig value < ɑ with a significant value of 0.000 < 0.05, which means the hypothesis is accepted. Based on the results of data analysis, there are two main conclusions. First, the combination of the Team Games Tournament learning model with Wordwall media significantly increases students' learning motivation on endocrine system material. Second, this combination also has a positive and significant impact on student learning outcomes. A significance value of 0.000 (<0.05) indicates that this model is effective in increasing student motivation and learning outcomes